Initiation locations of lightning flashes relative to radar reflectivity in four small Florida thunderstorms. Issue 12 (29th June 2017) - Karunarathna, Nadeeka; Marshall, Thomas C.; Karunarathne, Sumedhe; Stolzenburg, Maribeth
Abstract: This study examines initiation locations of intracloud (IC) and cloud‐to‐ground (CG) lightning near Kennedy Space Center, Florida, on 1 day. One unicellular and two multicellular thunderstorms occurred over land, and one multicellular storm was 30 km offshore. The storm over ocean was visible on radar 47–51 min before its first flash (of 17 total); first echoes in the storms over land were 23, 12, and 16 min prior to the first flashes (of 34, 16, and 9 total). Initiation points of 66 flashes were identified using the first initial breakdown (IB) pulse location from electric field change measurements or a VHF source coincident with the first IB pulse; 10 ICs occurred without enough data to similarly locate the initiation. All but 2 of 35 flashes that initiated as negative CGs began below 6.8 km altitude; two higher CG initiations (7.1–7.5 km) were the first CGs in two storms. Initiations of 21 normal ICs occurred above 7.9 km, 6 late stage ICs initiated at 5.5–7.5 km, and 4 hybrid IC‐CG flashes initiated as ICs at 6.6–8.1 km. Initiation locations were tightly clustered in small regions of each cell. Over land, early and mature stage flashes initiated within 2 × 2 km in each cell, or about 10–25% of the midlevel reflectivity coverage. One cell over ocean had initiations within 6 × 5 km, less than 30% of its reflectivity area. The IC initiations generally occurred above reflectivity cores, in 15–35 dB Z, and CG initiations were in 30–45 dB Z beside or atop cores. Plain Language Summary: Thunderstorms over ocean are relatively poorly understood due to scarce observations from ground‐based systems. This paper describes four small thunderstorms, three over land and one over coastal ocean, from one summer day in Florida. Inside these clouds, the initiation locations of 66 of the 76 intracloud (IC) and cloud‐to‐ground (CG) lightning flashes could be determined accurately. Most IC flash initiations, producing flashes that did not come to ground, occurred at 7.5–10.5 km altitude, above the region of greatest radar echo. Most CG flash initiations, producing flashes that did connect to ground, were at 4.5–7.5 km, beside or at the top of the strongest radar echo. In these storms the flash initiation locations over land and over ocean were quite similar, although the storm over ocean took 2 to 3 times longer to start making lightning. This study examined what may be considered a typical summer day in Florida, with many convective clouds in the area, but only a few that developed into thunderstorms. Among the storms studied, several cells did not produce any lightning. In terms of their radar echoes, these non‐lightning‐producing cells were weaker, shallower, and had no period of rapid upward growth compared to their lightning‐producing companion cells. Key Points: Most (24 of 31) IC initiations were above echo cores at >7.5 km altitude, and 33 of 35 CG initiations were beside or atop cores at <6.8 km IC and CG flash initiation locations were tightly clustered in small horizontal areas, much smaller than the >40 dB Z core reflectivity area Offshore storm had similar initiation altitudes as storms over land but had much longer early stage and time from first echo to first flash